The Disenchantment of Secular Discourse - Su, Anna (A journal of church and state, 2010)
Contemporary liberal democracy is at an ironic point of its evolution. It is Lockean in appearance but without his theological premises, while it is Rawlsian in its quest for an overlapping consensus, which, as it turns out most of the time, produces results so diluted that not all participants could claim them as part of their own respective truths., Steven Smith's most recent, thought-provoking work, The Disenchantment of Secular Discourse, exposes and dissects the gaping hole that this befuddling state of affairs has generated in current discourse in liberal democracies. Smith argues that modern-day conversations are carried within a “secular cage” that is too cramped to be able to substantively address issues that touch upon our most fundamental normative commitments.